The nutrition care needs of patients newly diagnosed with type 2 diabetes: informing dietetic practice. Issue 4 (20th January 2016) - Ball, L.; Davmor, R.; Leveritt, M.; Desbrow, B.; Ehrlich, C.; Chaboyer, W.
Abstract: Background: Understanding patients' experiences and preferences for health care is important with respect to informing how to provide best‐practice, patient‐centred care. The present study aimed to explore the perceptions of patients who have been recently diagnosed with type 2 diabetes regarding nutrition care received from dietitians. Methods: Ten individuals recently diagnosed with type 2 diabetes participated in three individual semi‐structured qualitative telephone interviews: at baseline, then at 3 and 6 months after recruitment. Data were analysed using content analysis at each time point and meta‐synthesis of findings over time. Results: Participants' initial interactions with dietitians were challenging and overwhelming as a result of the instructional nature of consultations. Many participants questioned the use of dietary guidelines to inform nutrition care because this was not adapted to the individual. Some participants valued receiving education on topics such as label reading and serving sizes; however, others considered that the nutrition care was rushed and overly directive. Very few participants perceived that an ongoing relationship with a dietitian would be useful, and limited interaction was planned beyond 6 months after diagnosis. Conclusions: These findings suggest that there is considerable opportunity for dietitians to enhance the nutrition care provided to patients with type 2 diabetes. Tailoring of dietary guidelines to individuals, utilising supportive counselling styles, and focusing on open communication in consultations that facilitate ongoing, useful care for patients, may help patients with type 2 diabetes achieve and maintain healthy dietary behaviours.